KOMBINASI METODE TOPSIS DAN SAW DALAM MENDUKUNG KEPUTUSAN SELEKSI KELAYAKAN PROPOSAL PENELITIAN DOSEN - Renna Yanwastika Ariyana; Erna Kumalasari Nurnawati; Luay Nabila El Suffa (IST AKPRIND Yogyakarta, 2018)
The selection process of research proposals is one of the important aspects carried out by each research institution in the University. The proposal selection phase is carried out so that each proposal submitted by each lecturer has the priority results of research proposals that meet the standard research standards that have been set, and the proposals submitted are eligible to obtain research funding. The proposal selection phase is carried out so that each proposal submitted by each lecturer has the priority results of research proposals that meet the standard research standards that have been set, and the proposals submitted are eligible to obtain research funding. In this study used a combination of TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution) and the SAW (Simple Additive Weighting) method in selecting research proposals submitted by lecturers. For the parameters used are the results of a review of the research proposal with the aim of looking at the suitability of the manual calculation with the method of the system being built. The results obtained by using 5 assessment criteria, it was found that the TOPSIS and SAW methods have a percentage of conformity between manual calculations with TOPSIS and SAW systems by 100%, this value was obtained from the test performed using 20 test samples by comparing manual calculations and system calculations who apply a combination of TOPSIS and SAW methods. The final stage of this study produces a prototype decision support system that can do the ranking in selecting the feasibility of the research proposal submitted by the lecturer by recommending proposals that are eligible to receive research funds based on the criteria and assessment weights set by each university.